Bond strength of three luting agents to zirconia ceramic - influence of surface treatment and thermocycling - Ahmed Attia (University of São Paulo, 2011)
OBJECTIVE: This in vitro study aimed to evaluate the influence of different surface treatments, 3 luting agents and thermocycling on microtensile bond strength (µTBS) to zirconia ceramic. Material and METHODS: A total of 18 blocks (5x5x4 mm) were fabricated from zirconia ceramic (ICE Zirkonia) and duplicated into composite blocks (Alphadent). Ceramic blocks were divided into 3 groups (n=6) according to the following surface treatments: airborne-particle abrasion (AA), silica-coating, (SC) (CoJet) and silica coating followed by silane application (SCSI) (ESPE Sil). Each group was divided into 3 subgroups (n=2) according to the 3 luting agents used. Resin-modified glass-ionomer cement (RMGIC, Ketac Cem Plus), self-adhesive resin cement (UN, RelyX Unicem) and adhesive resin cement (ML, MultiLink Automix) were used for bonding composite and zirconia blocks. Each bonding assembly was cut into microbars (10 mm long and 1±0.1 mm²). Seven specimens of each subgroup were stored in water bath at 37ºC for 1 week. The other 7 specimens were stored in water bath at 37ºC for 30 days then thermocycled (TC) for 7,500 cycles. µTBS values were recorded for each specimen using a universal testing machine. Statistical analyses were performed using a 3-way ANOVA model followed by serial 1-way ANOVAs. Comparison of means was performed with Tukey's HSD test at (α=0.05). RESULTS: µTBS ranged from 16.8 to 31.8 MPa after 1 week and from 7.3 to 16.4 MPa after 30 days of storage in water and thermocycling. Artificial aging significantly decreased µTBS (p<0.05). Considering surface treatment, SCSI significantly increased µTBS (p<0.05) compared to SC and AA. Resin cements (UN and ML) demonstrated significantly higher µTBS (p<0.05) compared to RMGIC cement. CONCLUSIONS: Silica coating followed by silane application together with adhesive resin cements significantly increased µTBS, while thermocycling significantly decreased µTBS.